Analisis Value Chain PT Perkebunan Nusantara V Dalam Mewujudkan Sustainable Competitive Advantage Usaha Kelapa Sawit - , Jojor Gustmainar ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Thesis contributes the condition of agro industry which needs strategy for achievement superior competitive advantage through ability understanding of what and how to explore companyâs resources and capabilities in crude palm oil business which would give value for potential buyer. PT Perkebunan Nusantara V is one of agro government corporate from consolidation PT Perkebunan II, IV and V. Company has decreased in profit and has frustrated in fresh fruit bunch price, sales volume made company commitment to restructure internal performance. According to value chain concept shows that primary activities as activities of production from input until finished good and also secondary activities as support in production process are companyâs competitive advantage which can be more develop as product portfolio through replanting in sustainability by using human local resources, implication of differentiation strategy and low cost strategy will make company can make mapping of strategy in expand product, market share, diversification and vertical integration. By going growth, keep stability and low cost strategy will made company acknowledge of companyâs resources and capabilities which give value for company and potential buyer and achieve sustainable competitive advantage in crude palm oil industry which has prospect as one of input alternative energy resources and food industry in global competition.